The Role Of Proactive Marketing In Improving Market Share (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to determine the role of proactive marketing in improving the market share, as the researcher conducted a field study on the centers of the Ematel company in the province of Lattakia. Among the results were:There is a statistically significant relationship between (radical innovation, risk management, market sensing, focus on customer learning, the ability to market communications, early competition efficiency) and improving the market share of Ematel in Lattakia Governorate.Through this study, the researcher recommended a set of proposals and recommendations that are expected to assist the specialized companies in understanding and consolidating the concept of proactive marketing and the possibility of its advancement in companies operating in this concept, especially the stage the Syrian market is going through, the most important of which are:Most companies are exposed to many risks that may threaten their future as a result of an unexpected occurrence, so it is necessary for the administrations of these companies to focus on knowing the causes of risk and confronting them in creative ways in order to add marketing value to all their activities.The research also found the need for companies to collect information on the requirements of customers and competitors, the market, the economic and political situation, and on the suppliers, due to the importance of marketing information in the process of making proactive marketing decisions.